TERRITORY MECHANISM IN THE OUTSIDE OF THE AKCAYA SETTLEMENT, PONTIANAK CITY - Ivan Adiel Abednego (Journal of Architecture&ENVIRONMENT, 2020)
Government policy in moving economic activities to spaces outside of settlements results in changes in the territory of the space used. This requires further regulation of territorial mechanisms that occur in research studies. The purpose of this research is to identify the characteristics of outer space territories and determine the mechanism of these outer territories. The strategy in this study used a qualitative strategy with observational research techniques, in-depth interviews, and documentation. Miles Huberman model analysis used in this research. The results obtained are 1) secondary territorial use of outer space by involving local and external users, 2) secondary mechanisms are used with limited time and activity control, cooperative ownership, and access to places that are open to outdoor users.